Binary solvent extraction of intracellular lipids from Rhodotorula toruloides for cell recycling - Jingyi Song; Rasool Kamal; Yadong Chu; Shiyu Liang; Zongbao K. Zhao; Qitian Huang (Biotechnology for Biofuels and Bioproducts)
Abstract Background Microbial lipid extraction is a critical process in the production of biofuels and other valuable chemicals from oleaginous microorganisms. The process involves the separation of lipids from microbial cells. Given the complexity of microbial cell walls and the demand for efficient and environmentally friendly extraction methods, further research is still needed in this area. This study aims to pursue the extraction of intracellular lipids from oleaginous yeasts using inexpensive solvents, without disrupting the cells and even maintaining a certain level of cell viability. Results The study used fresh fermentation broth of Rhodotorula toruloides as the lipid extraction target and employed a binary solvent of methyl tert-butyl ether (MTBE) and n-hexane for lipid extraction. The effects of extraction time and solvent ratio on cell viability, lipid extraction efficiency, and fatty acid composition were analyzed. Conditions that balanced lipid yield and cell survival were selected for lipid extraction. Specifically, using a binary solvent (with 40% MTBE) to extract an equal volume of R. toruloides fermentation broth achieved a total lipid extraction rate of 60%, while maintaining a 5% cell survival rate (the surviving cells served as the seed for the second round of lipid production). After separating the solvent phase and supplementing the lipid-extracted cells with carbon sources and a small amount of nitrogen sources, the cells gradually regained biomass and produced lipids. Repeating this "gentle" extraction on surviving and regrown cells and adding carbon and nitrogen sources can enable a second round of growth and lipid production in these cells. Conclusions This is an interesting finding that may potentially encompass the extraction mechanisms of polar/nonpolar solvents and the phenomenon of yeast autophagy. This method does not require the destruction of the cell wall of oleaginous yeast. The separation after extraction is simple, and both the cells and solvents can be recycled. It provides a possible approach for simultaneous fermentation and lipid extraction.